The Influence of Digital Competence on the Digitalization of Public Services: The Role of Digital Self-Efficacy Mediation and Work Innovation among Civil Servants in Kupang City - Tuti Setyorini; Janri Manafe; Krysler Adoe; M. L. Junior Boni Geti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the effect of digital competence on the digitalization of public services by considering the mediating roles of digital self-efficacy and innovative work behavior. The digitalization of public services requires the readiness of human resources, particularly civil servants (ASN), to master digital skills and to possess confidence and the ability to innovate in facing technological transformation. This research employs a quantitative approach using a survey method targeting civil servants in Kupang City who are involved in public service delivery. Data was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that digital competence not only has a direct impact on the digitalization of public services but also indirectly through the enhancement of digital self-efficacy and innovative work behavior. The findings provide both theoretical and practical contributions to strategies for strengthening civil servants’ capacity in supporting more effective and sustainable digital-based bureaucratic reforms.